2019
DOI: 10.12669/pjms.35.1.431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lymph node metastasis of thoracic esophageal squamous cell carcinoma on design of radiotherapy target volume

Abstract: Objective: To analyze the correlation between lymph node metastasis of thoracic esophageal squamous cell carcinoma (ESCC) and clinical and pathological factors, and to provide a reference for the outline of clinical target volume. Methods: The pathological characteristics of 1034 thoracic ESCC patients after surgery were described, and the correlations between clinical and pathological factors and lymph node metastasis were studied by univariate and Logistic multivariate analyses. Results: Lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our study observed a low LN metastase rate of 4.11% with a median of 2 metastatic LN (range, 1-20). Compared to Goubing Pan's study, the LN metastase rates for middle-third and lower-third ESCC were 30.7% and 15.7%, respectively (13). This demonstrates that NCRT signi cantly reduces the rate of LN metastases.…”
Section: Discussionmentioning
confidence: 64%
“…Our study observed a low LN metastase rate of 4.11% with a median of 2 metastatic LN (range, 1-20). Compared to Goubing Pan's study, the LN metastase rates for middle-third and lower-third ESCC were 30.7% and 15.7%, respectively (13). This demonstrates that NCRT signi cantly reduces the rate of LN metastases.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, an accurate outline of the target volume for lymphatic drainage is of great signi cance for delineating clinical target areas [17]. CTVs have two components: subclinical invasion and intramural metastasis of the primary tumor (CTVp) and subclinical lymph nodes (CTVn) [18].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Clinical diagnosis of cervical lymph node diseases is mainly arrived at through puncture and surgical pathology or though imaging examinations. 3,5 Fig. 2: Multiple enlarged lymph nodes were detected in right cervical region II, and the larger ones were about 2.3×1.3cm, cortex thickened, internal echo was disordered and uneven, and lymphatic hilum disappeared.…”
Section: Introductionmentioning
confidence: 98%
“… 2 , 3 Clinical diagnosis of cervical lymph node diseases is mainly arrived at through puncture and surgical pathology or though imaging examinations. 3 , 5 Because of the complex influencing factors of cervical LN enlargement, some patients cannot be diagnosed after puncture or surgical pathology examinations alone. 6 With the development of imaging techniques, CEUS and MRI have been widely used for diagnosing various tumoral diseases.…”
Section: Introductionmentioning
confidence: 99%